THE ULTRAMICROSCOPY OF THE SPLEEN STRUCTURE OF MATURE RATS IN ADMINISTRATION OF HYDROCORTISONE - Statsenko, L.; Sherstyuk, O.; Tihonova, O.; Deynega, T. (World of Medicine and Biology, 2015)
12 mature male rats have been involved into experimental study. Ultramicroscopic examination has revealed masses of spleen parenchyma following the administration of hydrocortisone. On day 7 of the experimental study the significant differences from intact animals have been noted, including reduced number of mitoses, narrowing of cisterns of endoplasmic reticulum, enlargement of collagenous fibers. The most apparent lesions have been observed in the structure of germinative centers and mantle zone of white pulp of spleen. The described lesions may indicate about a decrease of synthetic processes in the cell, reduction of its functional activity, induced by adrenal cortex hormone hydrocortisone.
Keywords: spleen; lymphocytes; ultramicroscopy